The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/anie.200461375
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Reaction of Crown Ether Complexes of Aqua(hydroxy)(aryl)iodonium Ions

Abstract: The Koser reagent, [hydroxy(tosyloxy)iodo]benzene (1; Ts = p-toluenesulfonyl), is a useful oxidizing agent for a range of organic substrates.[1] It has been reported that upon dissolution in water the l 3 -iodane undergoes complete ionization to give the hydroxy(phenyl)iodonium cation (PhI + OH).[2] The hydroxy(phenyl)iodonium ion does not form an ion pair with a tosylate ion and is presumed to be ligated with at least one water molecule at an apical site of the iodine(iii) center. This aqua(hydroxy)(phenyl)io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…This secondary intermolecular interaction is responsible for increasing the stability of this complex. The same group reported the aqua complexes of iodosylarenes 17 – 19 with one molecule of water coordinated to the hypervalent iodine, which were prepared by treatment of (diacetoxyiodo)­arenes with trimethylsilyl triflate or bis­(trifluoromethylsulfonyl)­imide in the presence of 18-crown-6 ether in dichloromethane. , Single-crystal X-ray study revealed that these aqua complexes also have the T-shaped structure with two apical positions of the iodine­(III) atom occupied by OH and one molecule of water. The presence of 18-crown-6 ether also has a stabilizing effect on iodine complexes (Figure ).…”
Section: Synthetic Applications Of Trivalent Iodine Compoundsmentioning
confidence: 99%
“…This secondary intermolecular interaction is responsible for increasing the stability of this complex. The same group reported the aqua complexes of iodosylarenes 17 – 19 with one molecule of water coordinated to the hypervalent iodine, which were prepared by treatment of (diacetoxyiodo)­arenes with trimethylsilyl triflate or bis­(trifluoromethylsulfonyl)­imide in the presence of 18-crown-6 ether in dichloromethane. , Single-crystal X-ray study revealed that these aqua complexes also have the T-shaped structure with two apical positions of the iodine­(III) atom occupied by OH and one molecule of water. The presence of 18-crown-6 ether also has a stabilizing effect on iodine complexes (Figure ).…”
Section: Synthetic Applications Of Trivalent Iodine Compoundsmentioning
confidence: 99%
“…We reported that the reaction of (diacetoxyiodo)benzene with trimethylsilyl trifluoromethanesulfonate (TMSOTf) in the presence of 18C6 in dichloromethane affords the aqua crown ether complex 6a in high yield (Scheme ) 18. The aqua complex 6a is soluble in dichloromethane, MeCN, and MeOH, but not in less polar diethyl ether and hexane.…”
Section: Synthesis and Structure Of Activated Iodosylbenzene Monomermentioning
confidence: 82%
“…Hu reported a copper-catalyzed oxidation of phenyl-triuoroborate, 20 Fensterbank a TEMPO-promoted procedure, 21 and Ochiai employed a hypervalent iodonium complex. 22 Of greatest relevance are Molander's oxidation conditions using Oxone 23 and Kandasamy's report using hydrogen peroxide in lactic acid for the oxidation of phenyl-triuoroborate. 24 These conditions, however, are relatively harsh and not consistent with the rapid, clean oxidations we observed.…”
Section: Resultsmentioning
confidence: 99%